Development of medium throughput muscarinic receptor binding assay - Yap, Kim Fah; Chung, Lip Yong; Mustafa, Mohd Rais (Penerbit Universiti Sains Malaysia, 2004)
Muscarinic receptors are members of the large family of G protein-coupled receptors (GPCRs). These receptors are widely distributed throughout the body and are responsible for numerous vital functions in both the brain and autonomic nervous system (Lefkowitz et al., 1990).